Smart Automatic Bed Sheets Stretcher / Ezreen Ayu Khatijah Azman ... [et al.] - Azman, Ezreen Ayu Khatijah; Basori, Noor Izyana; Abdul Razak, Ruskila; Zainol Ariffin, Siti Saudah; Wan Mohamad, Wan Ismahani (2018)
After some personal experiences towards rushing morning routine, the team had chosen a product that we believe may help us and many people to make their bed look tidy. The product is Smart Automatic Bed Sheets Stretcher. Office workers and students who love to stay up at night tends to have rush morning routine. They might not have enough time to stretch their bed sheets before they go to office or class.